MATH AND MATE IN JAVANESE PRIMBON: ETHNOMATHEMATICS STUDY - Utami, Niken Wahyu; Sayuti, Suminto A; Jailani, Jailani (Journal on Mathematics Education, 2019)
Marriage is an essential part of life for most people. In the Javanese tradition, great attention is paid to the weton of the couple through Javanese Primbon. It predicts the fate of the couple in the marriage. This prediction of the Javanese outcome after the wedding has some numerical values. Therefore, this study aims to uncover these numerical values using ethnomathematics. This research uses a qualitative method. Analyzing the Javanese Primbon documents is meant to explore the numerical value of Javanese people. Also, analyzing the data using the Javanese Primbon documents was not only based on the interpretation of the researcher but also the result of discussions with cultural and mathematical experts. This study proposes numerical values such as number bases, remainder theorem, modulo, and modulus of the congruence in formal mathematics, which is associated with matchmaking using Javanese Primbon.